Internalization of Islamic Values in Students’ Character Formation at PETAMA School, Pahang Malaysia - Meldawati Meldawati; Nurhayati Nurhayati; Dina Dahliana; Ana Binti Saufi (Ahlussunnah: Journal of Islamic Education, 2026)
This study aims to analyze the process of students’ character formation at PETAMA School, Pahang, Malaysia, and to identify the factors influencing such character development. The study employed a qualitative approach using a case study method conducted from December 2024 to May 2025 at PETAMA School, Pahang, Malaysia. The participants consisted of students and educators directly involved in the character-building process. Data were collected through observation, in-depth interviews, and documentation. Data validity was ensured through source triangulation, while data analysis employed the interactive model of Miles and Huberman. The findings reveal that character formation at PETAMA is carried out holistically through cognitive, affective, and psychomotor dimensions. The character-building process takes place through three stages: moral knowledge through the teaching of akhlaq, aqidah, fiqh, and teachers’ role modelling; value implementation through congregational prayers, honesty, responsibility, independence, reward and punishment systems, and supervision of social interaction boundaries; and habituation through structured daily routines. Students’ character formation is influenced by internal, external, and institutional factors. Internal factors include self-motivation, health conditions, and previous habits. External factors encompass the roles of teachers, family, peers, school environment, culture, language, and technology. Institutional factors include the discipline of congregational prayers, daily tazkirah, behavioral evaluation, and personal approaches. Overall, PETAMA develops a comprehensive, contextual, and Islamic values-based character education model that has the potential to serve as a reference for character education development in both formal and informal educational institutions.